Standards of care of management of diabetes among rural cohort in Sri Lanka - a descriptive study - Chathuranga, P.A.D.U.; Meegodawidanage, N.; Rathnayaka, T.M.; Luke, W.A.N.V.; Mettananda, K.C.D. (Sri Lanka College of Internal Medicine, 2021)
Introduction: Type 2 Diabetes mellitus (T2DM) is a challenge to health care leading to increase in morbidity and mortality. Objective: We conducted a descriptive study in rural Sri Lanka to assess the standards of care and disease control among patients with diabetes to identify areas for improvement. Methods: A retrospective follow-up study was conducted in five hospitals in Anuradhapura district. All type 2 diabetic patients, diagnosed and started on oral hypoglycemic drugs 24 months prior to recruitment, who attended the above clinics during the study period were enrolled to the study. Data on demographics, medications and blood sugar control were collected using an interviewer-administered questionnaire and perusing medical records. Drug compliance was studied using a self-administered questionnaire. Results: Control of Diabetes and other cardiovascular risk factors 2 years following initiation of oral hypoglycaemic drugs in 421 patients (19.2% male, mean age 58.3±10.4 years) were studied. Even after 2 years of medications, 48.2% were overweight, 34.0% obese and 53.9% were physically inactive. Prevalence of medication use among them were, metformin 96.7%, statins 64.1 % and anti-hypertensives 49.4%. Their mean Fasting Blood Sugar(FBS) was 139±54.3 mg/dl and Body Mass Index(BMI) was 26.5±4.5kgm-2. Poor compliance to medication was found in 60.3%. Sub-optimal risk factor control, FBS >130mg/dl, blood pressure >130/80mmHg, and LDL >100mg/dl were seen in 45.1.%, 19.94% and 16.1%, respectively. Conclusion: Even though majority were started on necessary medicines, FBS control was poor in this rural population. The reasons behind poor FBS control need to be studied and addressed to improve care of patients with diabetes in rural Sri Lanka.
Oral Presentation Abstract (OP03), 5th Annual Congress of the Sri Lanka College of Internal Medicine. 2021, 18th to 20th November Sri Lanka.
Keywords: Diabetes; Standards